Przetwarzanie danych osobowych do celów badań naukowych. Aspekty prawne - Pyka, Aleksandra (Studia Prawa Publicznego, 2019)
This article refers to the issue of personal data processing conducted in connection with scientific research and in accordance with the provisions of Regulation (EU) 2016/679 of the European Parliament and of the Council of 27 April 2016 on the protection of natural persons with regard to the processing of personal data and on the free movement of such data, and repealing Directive 95/46/EC (General Data Protection Regulation). It is not uncommon for the purposes of scientific research to process personal data, which is connected with the obligation to respect the rights of the data of the subjects involved. Entities conducting scientific research that process personal data for this purpose are required to apply the general regulation governing, among others, the obligations imposed on the controllers. The issue of personal data processing for scientific research purposes has also been regulated in national legislation in connection with the need to apply the General Data Protection Regulation. The article discusses the basics of the admissibility of data processing for the needs of scientific research; providing personal data regarding criminal convictions and offences extracted from public registers at the request of the entity conducting scientific research; exercising the rights of the data of the subjects concerned; as well as the implementation of appropriate technical and organizational measures to ensure the security of data processing. In addition, the article discusses the issue of anonymization of personal data carried out after achieving the purpose of personal data processing, as well as the processing of special categories of personal data. The topics discussed in the article were not discussed in detail, as this would require further elaboration in a publication with a much wider volume range.